“E vi dichiaro marito e moglie (o marito-e-marito o moglie-e-moglie)”. Una difesa durkheimiana del mariage pour tous - Guizzardi, Luca (SocietàMutamentoPolitica, 2017)
Usually, the main argumentation against the same-sex marriage drags the nature in: gay marriage is ‘contra Naturam’. But, what is Nature in and of the marriage bond? The sex of the two partners? The natural fact of the procreation? Thanks by the theory of the sexual division of labour, the author develops a durkheimian defence of the gay marriage goodness. Durkheim’s theory allows us to outline the natural elements of and in the marriage tie which go beyond the strictly contingency of the (hetero)sexuality as well as of the sexual reproduction. So, following Durkheim, the gay marriage is not only a juridical and normative transformation but, first of all, it is linked to the person’s relational ability and (relational) construction of a conscious self-identity.